A Study on the web portal industry - Park, Chan Soo (KDI School, 1999)
The word “portal” has become as much a part of the Internet’s vocabulary as the word “Web.” One of the big issues from 1994 to 1997 was the “Browser War” between Netscape and Microsoft. However, after 1998, companies began to take interest in how to develop the “Portal” to cause more visitors to spend more time at the site. According to Media Metrix, a media research company that provides monthly traffic rates (the number of visitors who access Web sites) for Web sites, portals dominate the highest ranking sites in the top 10 sites. Since traffic rate is the most important criteria to measure a successful Internet model, a “portal” must be the most successful Internet model. But the portal business model has not been defined clearly so far. Portals contain a wide variety of content in the form of news, information, links and many services, such as ordering flowers, books, and CDs or free e-mail and Web space. As locating desired material on the Internet continues to become more difficult, the value of fast, reliable and simple-to-use portals increases as well. The portals business is a highly competitive industry. The market for Internet products and services is also highly competitive. There are no substantial barriers for entry into these markets. As a result, competition will continue to intensify in the portal industry
Thesis(Master) --KDI School:Master of Strategy & International Management,1999